(untitled) (Research, Society and Development, 2023)
The present study sought to develop and validate a distance learning course for health professionals who work with the management of radioactive health waste, using an instructional design based on the Kemp, Morrison and Ross model. This is a methodological study for the elaboration and validation of a distance learning course using the Kemp, Morrison & Ross instructional design. The instructional design chosen to elaborate the EaD course consists of nine stages, which allow the participant to be introduced to a logical sequence of contents and through the modality manage to manage their study time, which is an important advantage for the professional. As a result of the study, a self-instructional course was developed with a total workload of 4 hours, with three learning units. At the end of each unit, it is necessary to carry out a summative evaluation as a criterion to advance to the next unit and, at the end of the course, a formative self-assessment and a summative evaluation by the student. Through the methodological path, it can be concluded that the result, which was a technical product, will contribute to the training and continuous improvement of health professionals.